2005
DOI: 10.2133/dmpk.20.435
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Biodisposition of Poly(vinyl alcohol) in Rats and Mice

Abstract: Poly(vinyl alcohol) (PVA) of various molecular weight (MW=10,560-116,600) was successfully labeled with fluorescein isothiocyanate isomer I (FITC) according to the method of de Belder and Granath. A high-performance size-exclusion chromatographic procedure was developed for the quantitative analysis of FITC-labeled poly(vinyl alcohol) (F-PVA) in biological samples. F-PVA (80 K) disappeared slowly from the blood circulation according to the first-order kinetics (t1/2=7 h) after intravenous injection to rats. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 23 publications
4
41
0
Order By: Relevance
“…PVA also provide a potential targetable drug delivery system. 15) Drug-polymer conjugates are potential candidates for the selective delivery of antineoplastic agents to tumor tissue. Incorporating acid-sensitive bonds between the drug and the polymer is an attractive approach because it ensures effective release of the polymer-bound drug at the tumor site.…”
mentioning
confidence: 99%
“…PVA also provide a potential targetable drug delivery system. 15) Drug-polymer conjugates are potential candidates for the selective delivery of antineoplastic agents to tumor tissue. Incorporating acid-sensitive bonds between the drug and the polymer is an attractive approach because it ensures effective release of the polymer-bound drug at the tumor site.…”
mentioning
confidence: 99%
“…49 Studies examining the fate of larger molecular weights of PVA have shown accumulation within the liver and spleen of rats. 50 From these collective studies it is clear that the molecular weight of the polymer should be as low as possible to ensure complete elimination. To date most studies have focused on intravenous administration of polymers and therefore in order to license a dissolvable microneedle product further investigation into the distribution and elimination following repeated intradermal (i.d.)…”
Section: Discussionmentioning
confidence: 99%
“…Functionalizing of PVA with FITC to make fluorescein-labeled PVA (F-PVA) was modified from Kaneo et al 23 with small alterations and can be seen in Fig. 1.…”
Section: Functionalization Of Polyvinyl Alcoholmentioning
confidence: 99%